The Relationship Between Parental Knowledge Levels and the Intensity of Giving Gadgets to Preschool-Aged Children.: Relationship Between Parental Knowledge Levels and the Intensity of Giving Gadgets to Preschool-Aged Children. - Putri, Prestasianita; Tri Afandi, Alfid; Yunita Lestari, Indah (Rajaki of Tulip Medika Publisher, 2025)
The increasing use of gadgets among preschool-aged children has become a growing concern for parents and educators. This study examines the relationship between parental knowledge levels and the intensity of gadget usage given to preschool-aged children. A cross-sectional design was employed, involving 52 parents of preschool-aged children selected through purposive sampling in an urban community. Data were collected using structured questionnaires that assessed parental knowledge levels regarding gadget usage and the frequency with which gadgets were provided to their children. Parental knowledge was categorized as either